Surgical management of caesarean scar pregnancy: a case report - Gautam, Savita Singh; Kaur, Manmeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Caesarean scar ectopic is one of the rarest of all ectopic pregnancies. The incidence of caesarean scar pregnancy (CSP), which was extremely rare till recent times, has been rising steadily. Case have more of such cases being published in medical literature now. It is defined as when a blastocyst implants on a previous caesarean scar. The incidence of caesarean scar ectopic has increased due to increase in number of caesarean deliveries. Early diagnosis of this can be done by using ultrasound. It is very important because a delay can lead to increased maternal morbidity and mortality. Early diagnosis leads to prompt management and improves the outcome by allowing preservation of future fertility. Magnetic resonance imaging (MRI) has important role when sonography is equivocal or inconclusive before therapy or intervention. Case are reporting a rare case of G2P1l1 with previous one caesarean delivery, diagnosed as caesarean scar ectopic pregnancy with the help of sonography. Patient underwent laparotomy and on histopathological examination caesarean scar pregnancy was confirmed. Due to the rarity of this condition, there are no specific guidelines available for its management.